(Invited) Manufacturing Microwave AlGaN/GaN High Electron Mobility Transistors (HEMTs) on Truly Bulk Semi-Insulating GaN Substrates. (23rd August 2016) - Piotrowska, Anna Barbara; Kaminska, Eliana Anetka; Wojtasiak, Wojciech; Gwarek, Wojciech; Kucharski, Robert; Zajac, Marcin; Prystawko, Pawel; Kruszewski, Piotr; Ekielski, Marek; Kaczmarski, Jakub; Kozubal, Maciej; Trajnerowicz, Artur; et al.
Abstract : The substrate of choice for high power microwave GaN-based devices is silicon carbide. However recently novel semi-insulating truly bulk GaN substrates with excellent crystalline and electrical parameters have been developed by Ammono S..A. These allow to elaborate AlGaN/GaN heterostructures with high electron mobility values and density of two-dimensional electron gas. Developed processing steps, especially planar isolation by ion implantation and formation of low resistivity regrown ohmic contacts enabled fabrication of high quality devices. An 1000 mA/mm on-state current density along with low 4.4 Ω/mm on-state resistance were achieved. For the devices with rectangular, 0.8 μm gate length the fMAG and fs were 31 GHz and 22 GHz. The maximum output power density was more than 4.15 W/mm in S-band.